A rare complication after inguinal hernia repair: testicular torsion - Özsağır, Yusuf Önder; Akça, Görkem; Horsanalı, Mustafa Ozan; Eren, Hüseyin; Dil, Eyüp (The European Research Journal, 2019)
Testicular torsion is the most common urological emergency characterized by reduced blood flow of the testis, often due to spermatic cord torsion occurring in adolescence. A 68-year-old male patient admitted our hospital emergency service with the complaint of acute scrotal pain for a week. On history, he had undergone right inguinal hernia repair with synthetic mesh one week ago. Due to reduced blood flow of right testicular artery on colored doppler ultrasonography, emergent surgery was performed. On intraoperative examination, 360 degree torsion of spermatic cord from distal to the mesh, thrombosis of right testicular artery and necrosis of testicular tissue was observed. After detorsion of right testis, absence of blood supply to the right testis was observed. According to these findings, right inguinal orchiectomy was performed. It should be kept in mind that persistent pain may be a sign of testicular torsion which may develop early after inguinal hernia repair with synthetic polypropylene mesh. In suspicious of testicular torsion because of persistent scrotal pain after inguinal surgery, scrotal colored doppler ultrasonography must be performed immediately and consulted to the urologist. Succeed results may be provided by multidisciplinary approach and early treatment.